Prognostic Markers of Myelodysplastic Syndromes - Yuliya Andreevna Veryaskina; Sergei Evgenievich Titov; Igor Borisovich Kovynev; Tatiana Ivanovna Pospelova; Igor Fyodorovich Zhimulev (Medicina, 2020)
Myelodysplastic syndrome (MDS) is a clonal disease characterized by multilineage dysplasia, peripheral blood cytopenias, and a high risk of transformation to acute myeloid leukemia. In theory, from clonal hematopoiesis of indeterminate potential to hematologic malignancies, there is a complex interplay between genetic and epigenetic factors, including miRNA. In practice, karyotype analysis assigns patients to different prognostic groups, and mutations are often associated with a particular disease phenotype. Among myeloproliferative disorders, secondary MDS is a group of special entities with a typical spectrum of genetic mutations and cytogenetic rearrangements resembling those in de novo MDS. This overview analyzes the present prognostic systems of MDS and the most recent efforts in the search for genetic and epigenetic markers for the diagnosis and prognosis of MDS.